Pengaruh terapi mindfulness terhadap tingkat stres pada pasien hipertensi: A systematic review - Safaruddin, Safaruddin; Christina, Tri Yahya; Sriwiyanti, Lilik; Handayani, Wiwik; Sakinah, Sri (Holistik Jurnal Kesehatan, 2025)
Background: Mindfulness therapy is a therapeutic approach that uses mindful practice to help individuals manage their thoughts, emotions, and bodily sensations in a healthy manner. Techniques such as compressions and mindful breathing have been shown to be effective in reducing stress levels, improving cognitive function, and supporting the management of chronic diseases such as hypertension. Purpose: To analyze the effect of mindfulness therapy on stress levels in patients with hypertension. Method: A systematic review and meta-analysis were designed to explore the relationship between mindfulness therapy, stress levels, and hypertension. Articles were selected based on PICO eligibility criteria and retrieved from three major databases: PubMed, Google Scholar, and ScienceDirect. Keywords used included "Mindfulness Therapy" AND "Stress Levels" AND "Hypertension" AND "Randomized Control Trial" AND "Healthcare." Inclusion criteria included full-text articles with a quasi-experimental study design published between 2010 and 2024. Article analysis was performed using PRISMA charts and Review Manager (RevMan) software version 5.3. Result: A meta-analysis of 10 articles from various countries, including India, Iran, the United Kingdom, the United States, and New Zealand, showed that mindfulness therapy has a positive effect on reducing stress levels in hypertensive patients. This therapy demonstrated an effect size of 0.23 times (Mean Difference = 0.23; 95% CI = -0.54-0.07; p <0.13). Furthermore, the relatively balanced distribution of effect estimates indicates no bias, as demonstrated by the balance between the left and right plots. Conclusion: Mindfulness therapy is increasingly recognized as an effective complementary therapy in the management of chronic diseases such as hypertension. Suggestion: Health workers are advised to integrate mindfulness therapy as a complementary approach in managing hypertension.   Keywords: Hypertension; Healthcare; Mindfulness Therapy; Stress Levels.   Pendahuluan: Terapi mindfulness merupakan suatu pendekatan terapeutik yang menggunakan latihan kesadaran penuh untuk membantu individu mengelola pikiran, emosi, dan sensasi tubuh secara sehat. Teknik seperti meditasi dan pernapasan sadar terbukti efektif dalam menurunkan tingkat stres, meningkatkan fungsi kognitif, serta mendukung pengelolaan penyakit kronis seperti hipertensi. Tujuan: Untuk menganalisis pengaruh terapi mindfulness terhadap tingkat stres pada pasien hipertensi. Metode: Systematic review dan meta-analysis yang dirancang untuk mengevaluasi hubungan antara terapi mindfulness, tingkat stres, dan hipertensi. Artikel diseleksi berdasarkan kriteria kelayakan PICO dan diperoleh dari tiga basis data utama, yaitu PubMed, Google Scholar, dan ScienceDirect. Kata kunci yang digunakan meliputi “Mindfulness Therapy” AND “Stress Levels” AND “Hypertension” AND “Randomized Control Trial” AND “Health Services.” Kriteria inklusi mencakup artikel full-text dengan desain penelitian quasi-experimental yang dipublikasikan pada periode 2010–2024. Analisis artikel dilakukan menggunakan diagram PRISMA dan perangkat lunak Review Manager (RevMan) versi 5.3. Hasil: Meta-analisis terhadap 10 artikel dari berbagai negara, antara lain Indonesia, India, Iran, Inggris, Amerika Serikat, dan Selandia Baru, menunjukkan bahwa terapi mindfulness memberikan pengaruh positif dalam menurunkan tingkat stres pada pasien hipertensi. Terapi ini menunjukkan ukuran efek sebesar 0.23 kali (Mean Difference=0.23; 95% CI=−0.54-0.07; p<0.13). Selain itu, sebaran estimasi efek yang relatif seimbang menunjukkan tidak adanya bias, yang ditunjukkan oleh keseimbangan antara plot kiri dan kanan pada analisis. Simpulan: Terapi mindfulness semakin diakui sebagai terapi pendamping yang efektif dalam penatalaksanaan penyakit kronis seperti hipertensi. Saran: Tenaga kesehatan disarankan untuk mengintegrasikan terapi mindfulness sebagai pendekatan komplementer dalam penatalaksanaan hipertensi.   Kata Kunci: Hipertensi; Layanan Kesehatan; Terapi Mindfulness; Tingkat Stres.